Level of oxytocin prior to rugby and handball matches: An exploratory study among groups of Polish players - Kociuba , M.; Ignasiak, Z.; Rokita, A.; Cichy, I.; Dudkowski, A.; Scislak, M.; Kochan, K.; Sebastjan, A.; Spinek, A.; Lorek, D.; Bogin, B.; Chakraborty, R.; et al. (Anthropological Review, 2023)
The aim of the present exploratory study was to assess the changes in urinary oxytocin (OT) concentration during the period between five days before, and on the day of match, among rugby and handball players. Nine male rugby players with a mean age of 27.62 years (SD = 4.21) and 18 male handball players with a mean age of 17.03 years (SD = 0.57) participated. Urinary oxytocin level was measured by ELISA immunoassay as a ratio to the concentration of creatinine [mg/ml] measured through colorimetric detection. The relative level of OT to creatinine (OT/CRE) significantly differed between the type of player (rugby or handball) but not between times of measurements. Significant differences were only between OT/CRE level in a day of match in rugby players and in 5 days before match in handball players (p<0.05). There was no change in oxytocin levels during the time periods between five days before and on the day of a match, in either of the two kinds of players. The change in oxytocin might be traceable during the match but not before a match and this perhaps depends on a more subtle context of competition, but not on the assumption of competition. Further studies are needed based on more homogenous group with higher number of matches.